2022
DOI: 10.3390/met12040666
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of Passivated CUSTOM450 and AM350 Stainless Steels for Aeronautical Applications

Abstract: Custom 450 stainless steel and AM 350 stainless steel are both precipitation hardening stainless steels, which are widely used in a variety of aerospace applications. The former steel exhibits very good corrosion resistance with moderate strength, whereas the latter is used for applications requiring high strength along with corrosion resistance. In this study, the corrosion behavior of CUSTOM 450 and AM 350 stainless steels passivated in (a) citric acid and (b) nitric acid solutions for 50 and 75 min at 49 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 82 publications
1
4
0
Order By: Relevance
“…The HHT analysis reveals this unstable passive layer, with the samples exhibiting localized corrosion preponderance. This outcome confirms the findings of Samaniego et al [15], who reported localized corrosion in the samples passivated in nitric acid. In contrast to the nitric acid-passivated PHSS, the citric acid-passivated PHSS showed a greater tendency toward localized corrosion.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The HHT analysis reveals this unstable passive layer, with the samples exhibiting localized corrosion preponderance. This outcome confirms the findings of Samaniego et al [15], who reported localized corrosion in the samples passivated in nitric acid. In contrast to the nitric acid-passivated PHSS, the citric acid-passivated PHSS showed a greater tendency toward localized corrosion.…”
Section: Discussionsupporting
confidence: 92%
“…However, the passivation in nitric acid presented a greater energy accumulation at the middle and high frequencies, indicating localized corrosion. In the research of Lara et al, Samaniego et al, and Gaydos et al [7,14,15,77,78], it was concluded that nitric acid raises the passive layer's chromium content, clearing MnS inclusions from the surface and raising the likelihood of individual pitting. Because of the presence of MnS, the samples passivated in nitric acid in this study showed higher corrosion than those passivated in citric acid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stainless steel has been widely used in various applications because of its excellent mechanical properties, corrosion resistance and good welding performance, such as biomedical equipment, nuclear industry components, precision instruments, aviation, automotive industry, batteries and so on [73][74][75][76][77][78]. The welding of stainless steel usually does not require pre-welding or post-welding heat treatment, because unlike low-carbon steel alloy, there is no Martensite structure in HAZ [79].…”
Section: Welding Of Steel Battery Housingmentioning
confidence: 99%
“…Past research [26][27][28][29][30] demonstrated that the natural passive layer of titanium is susceptible to Cl − ion attacks because the diffusion of Cl − ions weakens the oxide layer. The presence of Cl − and OH − in passive materials increases the corrosion rates by interstitial penetration [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%